A Closer Look at Students’ School Climate Perception: A Case Study of Urban and Rural Ukraine during COVID-19 - Klimanska, Maryna; Shchudlo, Svitlana; Mirchuk, Iryna; Zelena, Oksana; Haletska, Inna; Klymanska, Larysa; Herasym, Halyna; Savka, Viktor; Okulicz-Kozaryn, Katarzyna (Journal of Education Culture and Society, 2024)
Aim. This study analyses the impact of adaptive quarantine during the COVID-19 pandemic on the perception of school’s social climate by students in more or less urbanised areas. Methods. The data was collected in 2016 (before the pandemic, n=1801) and in 2020 (during the pandemic, n=2038) among randomly selected 9th-grade classes (mean age=14) in a large city (Lviv), a small town (Drohobych), and rural areas (Drohobych raion). Generalised linear regression mixed modelling was applied to assess the impact of gender, location, year of the survey, and for the 2020 - for the quality of coping with the pandemic situation – and the interactive effect of these factors on the variability of school climate perception. Results. Before the pandemic, the acceptability of school climate was the highest in rural areas and the lowest in the city. During the pandemic, it decreased among students from rural areas and increased in towns. Students who perceived COVID-19 pandemic restrictions as more burdensome evaluated their school climate more positively than students who coped well with the pandemic. Conclusion. The impact of the tense pandemic situation on the attitude of adolescents to school was complex and probably reflected the inequality in the education system in urban and rural areas.